Science in an enchanted world philosophy and witchcraft in the work of Joseph Glanvill - Davies, Julie Anne (Routledge research in early modern history, 2018)
Best known as the Saducismus triumphatus (1681), Joseph Glanvill's book on witchcraft is among the most frequently published from the seventeenth century, and its arguments for the reality of diabolic witchcraft elicited passionate responses from critics and supporters alike. Davies untangles the intricate development of this text and explores how Glanvill's roles as theologian, philosopher and advocate for the Royal Society of London converge in its pages. Glanvill's broader philosophical method and unique approach to the supernatural provide a case study that enables the exploration of the interaction between the rise of experimental science and changing attitudes to witchcraft